Oswestry Disability Index scores correlate with MRI measurements in degenerating intervertebral discs and endplates. (17th October 2019) - Arpinar, V. Emre; Gliedt, Jordan A.; King, Jeffrey A.; Maiman, Dennis J.; Muftuler, L. Tugan
Abstract: Background: Low back pain (LBP) is a widespread problem and the leading cause of disability worldwide. While the cause of LBP is multifactorial, several studies suggested that inflammatory mediators in damaged subchondral plates of degenerating discs may lead to chemical sensitization and mechanical stimulation, eventually causing pain. The goal of this study was to explore associations between such changes and LBP‐related disability using dynamic contrast‐enhanced MRI. Methods: Thirty‐two patients diagnosed with nonspecific LBP and 24 healthy control subjects were studied with dynamic contrast‐enhanced (DCEMRI) MRI and T1r (spin–lattice relaxation in the rotating frame) acquisitions. DCEMRI enhancement in disc endplate regions and average T1ρ measurements in the nucleus pulposus were extracted. The LBP patients were grouped based on their Oswestry Disability Index (ODI) scores and associations between MRI measurements and ODI scores were analyzed. Results: Significant associations were found between ODI scores and DCEMRI enhancement in the cartilaginous endplate regions of the most degenerated discs. ODI scores also correlated with T1ρ measurements in the nucleus pulposus of degenerating discs. Conclusions: DCEMRI enhancement in the cartilaginous endplate regions and lower T1ρ measurements in the nucleus pulposus (NP) were associated with greater disability that is related to low back pain as reported on the ODI. This complements earlier reports suggesting a link between LBP and endplate degeneration. Further studies are needed to validate these findings. Significance: Our findings indicated that dynamic contrast‐enhanced MRI signal enhancement in the cartilaginous endplate regions were associated with greater disability related to low back pain. This signal enhancement might be an indication of inflammatory changes in disc endplate regions. Therefore, advanced quantitative imaging techniques like the ones presented in this study might be needed to complement conventional radiological evaluations to identify the subset of patients who could potentially benefit from novel therapies directed towards treating the disc endplate regions.